Inventory and Analysis of Diversity of Insect on Shallot Cultivation in Saruran Hamlet, Enrekang Regency - Kurnia, Nani; Lodang, Hamka (Jurnal Biologi Tropis, 2024)
Shallots (Allium ascalonicum L.) are a highly popular plant both as a culinary spice and herbal medicine. Due to their economic benefits, many farmers cultivate them. Saruran Hamlet, located in Anggareja District, Enrekang Regency, is one of the areas where shallots are intensively cultivated. Farmers face a significant problem with high pest infestation rates. To manage this, chemical pest control using insecticides is employed. However, insecticides are toxic and increasingly expensive. To reduce pesticide use, pest control using light traps was implemented through the "electricity to the fields" program by the local PLN. The use of light traps is suspected to have a negative impact on the balance of biotic ecosystem components, thus necessitating a study on this matter. Therefore, the aim of this study is to inventory and analyze the diversity of insect species in shallot cultivation areas in Saruran Hamlet, Enrekang Regency. This research employed a survey method by collecting insects trapped in farmers' light traps. The identification and counting of insect species were conducted in the FMIPA UNM Laboratory. Based on the collected data, the Shannon-Wiener diversity index (H’) was analyzed. The results showed that the total number of trapped insect individuals was 1,332, consisting of 27 species from 8 orders. The Shannon-Wiener diversity index (H’) was found to be 2.20, which falls into the moderate category.